2008
DOI: 10.1007/s00221-008-1475-9
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding moving obstacles

Abstract: To successfully move our hand to a target, we must consider how to get there without hitting surrounding objects. In a dynamic environment this involves being able to respond quickly when our relationship with surrounding objects changes. People adjust their hand movements with a latency of about 120 ms when the visually perceived position of their hand or of the target suddenly changes. It is not known whether people can react as quickly when the position of an obstacle changes. Here we show that quick respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…Why did our subjects respond to the rotation of the ball at all? An interpretation that would be consistent with earlier studies (Day and Lyon 2000; Pisella et al 2000;Aivar et al 2008;van Mierlo et al 2009) is that the initial response was an automatic reaction to motion of the selected points on the surface of the ball. The response was aborted after an additional 40 ms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Why did our subjects respond to the rotation of the ball at all? An interpretation that would be consistent with earlier studies (Day and Lyon 2000; Pisella et al 2000;Aivar et al 2008;van Mierlo et al 2009) is that the initial response was an automatic reaction to motion of the selected points on the surface of the ball. The response was aborted after an additional 40 ms.…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, when confronted with a moving obstacle during a goal-directed movement, people initially follow the motion of the obstacle. If doing so is inappropriate, they correct the response ϳ50 ms later (Aivar et al 2008). Similarly, when instructed to respond to a target jump by moving in the opposite direction than the target, people briefly follow the target before moving in the opposite direction (Day and Lyon 2000).…”
mentioning
confidence: 99%
“…In the study by Paulignan et al (1991), subjects were able to instantly modulate, by relying on visual feedback, the arm and hand movements with respect to online perturbations of the position and shape of the target object, with only minimal increase in the response time (∼100 ms) compared with motion in the absence of perturbations. Aivar et al (2008) studied adjustments of the hand movements with respect to abrupt online perturbations of obstacles and/or the target. They found similar latencies to those reported by Paulignan et al (1991) for the responses to the perturbations of the target position and slightly longer adaptation latencies for the obstacles.…”
Section: The Role Of Visual Information In Guiding Manipulationmentioning
confidence: 99%
“…Rothkopf and Ballard (2009), who studied human navigation in an immersed graphic environment, reported that subjects fixate the edges of obstacles for the purpose of planning a walking path for obstacle avoidance. Aivar et al (2008) provided evidence that fast arm responses to the displacement of obstacles are triggered by a reaction to retinal motion of moving obstacles. Many important questions still remain unanswered.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation